KOMUNIKASI SIMBOL : PECI DAN PANCASILA - Rama Kertamukti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
The use of peci in the activities of the community in Indonesia is an equivalent form of the symbol of amity and simple. Amity and the simplicity of it is visible in the form of a caps which usually contains only one element of black color and the shape of a tube-like caps follow the head of its users. The use of caps or songkok in Indonesia has been regarded as the culture (Pancasila). Caps in Indonesia became a symbol of resistance in a simplicity pattern to form a balance in society concerned with the material. Black in a psychology color have stimuli the nature of human emotion strong and have expertise are defined although official or formal. Symbolism key of mental life typical human and exceeding tiers animal of economics. Basic needs will symbolization clear in humans serves continuously and is a process of fundamental the human mind. As users and interpreter of symbol, human sometimes irrational to think of as if there natural of a connection between a symbol with what symbolized.